2020
DOI: 10.3390/su12166405
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Willingness To Pay for Proenvironmental Attributes of Biogas Digestate-Based Potting Soil

Abstract: Biogas from anaerobic digestion has become an important element in the renewable energy portfolio of many countries. In anaerobic digestion, digestate is produced as a byproduct. This could be used to produce fertilizers and potting soils for home gardeners substituting mineral fertilizers or peat-based products. However, this depends on consumer willingness to pay (WTP) for such products, which we investigate in this study. To this end, we conducted a discrete choice experiment (DCE) with 507 private consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…When DCEs were first introduced, it was only possible to evaluate these experiments on an aggregate level [35], but the development of Hierarchical Bayes (HB) estimation techniques has opened new and more sophisticated possibilities. Using HB allows a researcher to calculate part-worth utilities on a pseudo-individual level [36][37][38], even if there is little data for each respondent [39].…”
Section: Consumer Preferences and Wtp For Sngmentioning
confidence: 99%
See 2 more Smart Citations
“…When DCEs were first introduced, it was only possible to evaluate these experiments on an aggregate level [35], but the development of Hierarchical Bayes (HB) estimation techniques has opened new and more sophisticated possibilities. Using HB allows a researcher to calculate part-worth utilities on a pseudo-individual level [36][37][38], even if there is little data for each respondent [39].…”
Section: Consumer Preferences and Wtp For Sngmentioning
confidence: 99%
“…Although this might seem unrealistic given current market prices, this level was included to cover unreserved aversion toward a renewable gas product (opting against it although there is no price increase). The upper limits had to be chosen at a level that would include all accepted price premia in order to avoid under-coverage (as, e.g., in [39]). For biomethane, market prices from [49] were used and varied; for SNG, the calculated production costs came from [58].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Pappalardo et al (2019) noted that the willingness to pay (WTP) for the digestate depends on how much information is available among farmers. Although past studies have shown that farmers and/or consumers are willing to entry the digestate market (Dahlin et al, 2015;Herbes et al, 2020b), and purchase it (Selvaggi et al, 2021), understanding what drivers play a relevant role in the digestate purchasing process remains an open question, especially regarding the motivations that may influence its purchase instead of other soil conditioners like manure traditionally used and already well-known among consumers.…”
Section: Introductionmentioning
confidence: 99%
“…This policy aims to achieve a 32% share of renewable energy from total energy consumption by the year 2030 [1][2][3]. In consequence, this leads to a huge production of biogas plant byproducts, digestate, a renewable resource [4] which requires post-treatment for nutrient recovery to meet the latest European Union regulation proposal on fertilizers [3,5].…”
Section: Introductionmentioning
confidence: 99%